IMPLEMENTASI SEO WEB DESIGN METHODOLOGY PADA OFFICIAL HOMEPAGE PONDOK PESANTREN QODRATULLAH - Ependi, Usman (JURNAL ILMIAH MATRIK, 2013)
Homepage or website for an organization is a way to deliver information to the public. Now the number of homepage or website of the day is always increasing both personal or owned by the organization. To communicate or disseminate information homepage/ website Islamic Boarding School of Qodratullah need a surefire way to use the Search Engine Optimization Web Design Methodology. Conducted with the implementation of the Search Engine Optimization Web Design Methodology on the homepage/ website Islamic Boarding School of Qodratullah website is expected to compete with other websites. In addition, the information on the homepage/ website Islamic Boarding School of Qodratullah can be easily accessed by the public. Keyword: Implementation, SEO, Official Homepage, and PP Qodratullah